Cognitive Bias and Its Relationship to the Level of Information Processing among Umm Al-Qura University Female Students - Alharbi, Ehklas Ahmed; Alharbi, Newar Mohammed Saad (Journal of Educational and Psychological Sciences, 2023)
The study aims to identify the level of both cognitive bias and the level of information processing; to reveal the relationship between them among Umm Al-Qura University female students; to reveal the differences in cognitive bias and the levels of processing attributed to the (specialization, academic year, academic achievement) variables, and the predictability of the levels of information processing through cognitive bias. The study sample consisted of (387) female students selected through stratified random method from various academic disciplines. The descriptive approach was applied. The cognitive bias scale developed by Van der Gaag et al. (2013), Arabized by Al-Hamouri (2017), and the information processing level scale developed by Al-Harbi (2022) were used. The study reached the following findings: The study sample showed an average level of cognitive bias and a high level of deep information processing; there was a positive relationship between cognitive bias and the level of information processing, with no statistically significant differences attributed to the (specialization, academic year, academic achievement) variables in the total score and dimensions of the cognitive bias scale and the information processing level scale, and the predictability of the level of information processing through cognitive bias. Based on the findings of the present study, it recommends directing the interest of those in charge of the educational process to enrich the curricula with educational and training programs aimed at developing skills that contribute to reducing cognitive bias and enhancing the level of deep processing among university students.
Keywords: cognitive bias; the level of information processing; Female students of Umm Al-Qura University